2010
DOI: 10.1901/jaba.2010.43-333
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Stimulus Control Over a Communication Response as an Intervention for Stereotypical Responding

Abstract: Stereotypical behavior maintained by automatic reinforcement often does not result in harm but may be undesirable in some situations. In the current investigation, participants were 2 individuals who engaged in nonharmful stereotypical responses shown in an analogue functional analysis to be insensitive to social contingencies. After bringing these responses under stimulus control using differential punishment, both participants learned a mand to terminate punishment for stereotypy. We also assessed whether th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Multiple schedules have been combined with treatment interventions (e.g., FCT) to treat problem behavior maintained by access to adult attention (Fisher et al, 1998; Rooker et al, 2013), access to tangible items (Betz et al, 2013; Hagopian et al, 2005), access to edible items (Jarmolowicz, DeLeon, & Contrucci Kuhn, 2009), interruption of ritualistic behavior (Rispoli, Camargo, Machalicek, Lang, & Sigafoos, 2014), escape from academic instruction (Álvarez et al, 2014), and problem behavior maintained by automatic reinforcement (Anderson et al, 2010; Doughty et al, 2007). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple schedules have been combined with treatment interventions (e.g., FCT) to treat problem behavior maintained by access to adult attention (Fisher et al, 1998; Rooker et al, 2013), access to tangible items (Betz et al, 2013; Hagopian et al, 2005), access to edible items (Jarmolowicz, DeLeon, & Contrucci Kuhn, 2009), interruption of ritualistic behavior (Rispoli, Camargo, Machalicek, Lang, & Sigafoos, 2014), escape from academic instruction (Álvarez et al, 2014), and problem behavior maintained by automatic reinforcement (Anderson et al, 2010; Doughty et al, 2007). …”
Section: Resultsmentioning
confidence: 99%
“…For many applications, although the primary concern was problem behavior such as self-injurious behavior (SIB) or aggression, the dependent variable that was evaluated using a multiple schedule was an FCR or other appropriate behavior (e.g., requesting teacher attention). Therefore, we categorized response topographies as FCR (i.e., an alternative communicative response taught during FCT; e.g., Fisher et al, 1998; Hanley et al, 2001), socially appropriate behavior (i.e., an existing appropriate response that occurred at high rates or at inappropriate times; e.g., Tiger & Hanley, 2004, 2005), or problem behavior if the investigators included a specific problem behavior in the multiple-schedule evaluation (e.g., Anderson et al, 2010). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the arbitrary reinforcement (i.e., praise) and punishment, in the form of a reprimand, associated with the multiple schedule were sufficient to maintain appropriate walking despite the continuous availability of the functional reinforcer. Although previous research has demonstrated discriminative control over behavior using a nonfunctional reinforcer in the context of a multiple schedule (cf., Anderson, Doughty, Doughty, Williams, & Saunders, ; Doughty, Anderson, Doughty, Williams, & Saunders, ; McKenzie et al, ; Piazza et al, ; Rapp et al, ), these studies have not focused specifically on toe walking.…”
Section: Discussionmentioning
confidence: 99%
“…These interventions targeted loud or repetitive vocalizations (Athens, Vollmer, Sloman, & Pipkin, 2008;St. Peter et al, 2005;Shaw & Simms, 2009), tongue protrusion and tongue chewing (Rosine & Martin, 1983), and motor stereotypy (Anderson, Doughty, Doughty, Williams, & Saunders, 2010;Rapp, Vollmer, Peter, Dozier, & Cotnoir, 2004). The most common approaches in these studies were aversive: positive punishment taking the form of a visual cue (Shaw & Simms, 2009), response blocking (Anderson et al, 2010), and contingent demands (Athens et al, 2008) combined with other procedures.…”
Section: Repetitive Behavior In Down Syndromementioning
confidence: 99%